Crossed Czerny–Turner Spectrometer with Extended Spectrum Using Movable Planar Mirrors. Issue 5 (May 2018) - Sze, Jyh-Rou; Wei, An-Chi
This study reports a crossed Czerny–Turner spectrometer with multiple mirrors to extend the inspected spectrum. A design example with two movable mirrors and a stationary planar mirror is experimentally demonstrated to offer two additional spectral bands, thereby leading to thrice the spectral range of the original Czerny–Turner spectrometer. The results indicate that the configurations to measure the three bands have almost identical parameters. The moving direction of the planar mirror and the plane of incidence are orthogonal; thus, the influence of mirror movement on the repeatability of the spectrum is minimized. In addition to the merits of cost-effectiveness and rapid inspection, the reported mechanism of mirror movement is applied to general spectrometers to extend the spectral coverage without sacrificing the resolution.